Fatigue Berhubungan dengan Kualitas Hidup pada Pasien Gagal Jantung - Rissa Latifardani; Dian Hudiyawati (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between fatigue and quality of life in heart failure patients. This study uses a correlative descriptive method utilizing a cross-sectional approach. Based on the study's results, most respondents were in the age range of 56-65 years with 39.6% and male sex as much as 61.3%. Most respondents are in the category of severe fatigue 77.4% and poor quality of life as much as 70.8%. Data analysis used the Chi-Square test, which produced a p-value of 0.001. In conclusion, a relationship exists between fatigue and quality of life in heart failure patients. Keywords: Heart Failure, Fatigue, Quality of Life